2015
DOI: 10.1111/chd.12282
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Depression Symptoms with Alcohol and Smoking Tobacco Use in Adult Patients with Congenital Heart Disease

Abstract: Self-reported depressive symptoms are associated with increased alcohol and smoking tobacco use by ACHD patients. Alcohol use may be a means of self-medicating for untreated depression, but further investigation is needed. Risk factors, including depressive symptoms and substance use, should be routinely assessed and addressed in ACHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
4
10
1
Order By: Relevance
“…The observed difference in weekly alcohol intake was not statistically significant between the high and low level depression groups participants, and in fact was less in participants with depression. This finding differs from previous research which has identified an association between increased alcohol consumption and depressive symptoms [ 40 ]. It is difficult to explain this result, but it might be related to the multi-comorbid conditions of the participants in this study, which may require a restriction in alcohol intake.…”
Section: Discussioncontrasting
confidence: 99%
“…The observed difference in weekly alcohol intake was not statistically significant between the high and low level depression groups participants, and in fact was less in participants with depression. This finding differs from previous research which has identified an association between increased alcohol consumption and depressive symptoms [ 40 ]. It is difficult to explain this result, but it might be related to the multi-comorbid conditions of the participants in this study, which may require a restriction in alcohol intake.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our findings, borderline personality disorder is stated to be associated with smoking or smoking continuation (28). Other studies have also considered relationship between borderline personality and smoking or substance use (29). Those in the borderline personality disorder are prone to significant emotional instability that may be considered as an explanation for the chance to experiment in smoking.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, for regular smoking and for-ever use of cannabis, the correlation with borderline personality traits has been explained by common genetic factors (29). The cross-sectional nature of the study design may lead to selective survival bias and hinder drawing causal relationships.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…Oral health is no exception, as such patients often present oral pathologies specific to their condition or to other external factors [8]. There also appears to be a positive association between depression and alcohol and tobacco use in the general population [9].…”
Section: Introductionmentioning
confidence: 99%